Designing a Batak Toba Local Content Educational Game Prototype: A GDLC-Based User Needs Analysis Approach - Monalisa Pasaribu; Juli Yanti Damanik; Tiurma Lumban Gaol; Rudy Chandra; Valisneria Utami (Institute of Multidisciplinary Research and Community Service, 2026)
Digital-based educational games that incorporate local content have significant potential as interactive and engaging learning media, particularly in introducing local culture to users as well as understanding their own culture and serving as a form of appreciation and strengthening of national identity. Currently available educational game applications, however, are limited to a few particular cultures, with less attention to integrating local elements, particularly those of the Batak Toba culture. This study aims to identify the necessary features, design, and gamification models, as well as the factors influencing the effectiveness of educational games in enhancing understanding of local content, using the Game Development Life Cycle (GDLC) method with the addition of user needs analysis. The user needs analysis was conducted using a survey and Focus Group Discussions (FGD) with prospective user partners at primary schools in Toba. The user needs analysis indicated a need for a mobile application with interactive, user-friendly features. More than 33% chose adventure, with some challenges and trophies, to be played individually or as part of a team. Furthermore, the results of the survey and FGD served as the basis for the pre-production phase, which determined the game type, scenario, gameplay, and challenges. In the production phase, the game interface was designed according to user needs. The final stage of prototype testing indicated that 95% of respondents stated that the prototype depicted Batak cultural content. This research contributes to the implementation of GDLC by integrating user needs analysis into data collection to increase software satisfaction and acceptance. Further research is needed to analyze system testing and the application's impact on students' knowledge of the Batak Toba subject. Keywords: Local content, Educative game, User analysis, Culture, Gamification.